A study of the doped zinc-ferrite nanoparticles with bismuth. (11th July 2018) - Shoushtari, Morteza Zargar; Emami, Akram; Ghahfarokhi, Seyed Ebrahim Mosavi
Abstract: In this article, the doped zinc-ferrite nanoparticles with bismuth by using glycine as a fuel have been made by using the microwave combustion method. After synthesizing the ZnFe2−x Bix O4 samples with x = 0.0, 0.02, 0.04, 0.06, 0.1, 0.15, dielectric properties such as dielectric constant, dielectric loss factor, and also conductivity ( σ a c ) were measured by using a LCR meter in the frequency range of 0–10 MHz. The results showed that the dielectric constant decreases with increasing the frequency; then its value reaches a constant magnitude. Also we considered the structural, morphological and magnetic properties of nanoparticles by using the x-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and vibrating sample magnetometer (VSM), respectively. The optical properties of the sample were studied by using the visible-ultraviolet light (UV–vis) spectroscopy. The results of the XRD patterns showed no additional peak was observed in the samples, and this revealed that the samples are single-phase. Also these results showed that the lattice parameter increases with increasing the bismuth concentration. SEM results showed an ascending trend in the size of the nanoparticles. Also, considering the VSM results characterized that increasing the bismuth amount leads to lower saturation magnetization, coercivity and remaining magnetization of the samples. The results of UV–vis spectroscopy showed that increasing bismuth amount can increase the sample optical band gap.